Environment News Broadcast in Malaysia: An Analysis of Prime -Time News Coverage In Local Television Channels. - Prasad, N.V.; Muhammad Tabut, Muhammad Hatta; Yesudhasan, Thomas Jayaprakash; Dollah, Mohd. Zain (2009)

(untitled)
This paper examines the representation of environmental news and analyses how the environment is being covered in local Malaysian television channels in their prime-time news broadcast.